Management of Avabahuka (Frozen Shoulder) with Ayurveda and Traditional Medication: A Case Study - Hewageegana, H G S P; Weerasekare, K R (British Journal of Healthcare and Medical Research, 2023)
Avabahuka is considered to be an Urdhva-chatrugata Vata vikara caused by vitiation of Vata dosha in Ansa Pradesha or Ansa Sandhi (shoulder joint)by Acharya Sushruta under 80 types of Vatavyadhi. Avabahuka can correlate with Frozen Shoulder which affects the glenohumeral joint, possibly involving a non-specific chronic inflammatory reaction. The onset of frozen shoulder is usually gradual and idiopathic. Causative factors for Avabahuka are not mentioned separately in Ayurveda texts but mainly Aharaja, Viharana and Abhighataja are three main groups. Samprapti of Avabahuka is caused by purely Vata dosa and soshana of Sleshaka kapha. In Ayurveda, there are many methods of treatments for Avabahuka as Siravedha, Agnikarma, Vasti chikitsa, Nasya, Snehana, Swedana and oral medication. Here, the case of 58 years old female patient, diagnosed as Avabahuka and managed successfully according to Ayurveda principles using Ayurveda and Traditional medicines. Initially, the patient was having severe pain, restricted movements of the right shoulder joint and stiffness, and after this treatment regimen, all symptoms reduced and returned to almost normal. This case study shows that Ayurveda and Traditional medicines used in Sri Lanka have effective treatments to cure the chronic disease Avabauka.